Records management of a typical state judiciary in Nigeria (1998)
The study is aimed at investigating the management of legal records in Nigeria with special reference to the Oyo State Judiciary. Questionnaire, interviews and direct observation methods were used for data collection. The study revealed that the state judiciary generates and receives records of various types such as case files, probate files, record books, cause books and registers. These records are in paper format. The records life-cycle concept was not applied to the management of the legal records. Also, there was no records retention and disposition schedule, the records centre operations are not performed, records appraisal was never done, and the filing system in use was alpha-numeric and chronological.